Hepatic Proteomic Analysis Reveals That Enhanced Carboxylic Acid Metabolism and Oxidoreduction Promote Muscle and Fat Deposition in Muscovy Duck - Wanli Yang; Xingyong Chen; Congcong Wei; Yutong Zhao; Zhengquan Liu; Zhaoyu Geng (Animals, 2021)
Liver is responsible for 90% of lipid synthesis in poultry; thus, it plays an important role in the growth of Muscovy ducks, which have a high fat deposition ability in a time-dependent manner. Therefore, male Muscovy ducks at 14, 28, 42, and 56 days were selected for body weight (BW), carcass weight (CW), subcutaneous fat thickness (SFT), abdominal fat weight (AFW), intramuscular fat content (IMF), and breast muscle fiber (BMF) diameter and density determination. Two-dimensional electrophoresis (2-DE) combining liquid chromatography linked to tandem mass spectrometry (LC-MS/MS) was used to analyze proteomic changes in liver at each stage. The BW, CW, AFW, SFT, and BMF diameter and density were significantly increased, while IMF content was significantly decreased at 28 to 42 days of age (p < 0.05). There were 57 differentially abundant protein (DEP) spots representing 40 proteins identified among the ages, in which 17, 41 and 4 spots were differentially abundant at 14 vs. 28, 28 vs. 42, and 42 vs. 56, respectively. Gene Ontology enrichment analysis found that DEPs were mostly enriched in the oxidation-reduction process, carboxylic acid metabolism, etc. Protein–protein interaction showed that catalase (CAT), triosephosphate isomerase (TPI), and protein disulfide-isomerase (PDI) were the key proteins responsible for the growth of Muscovy duck. In conclusion, 28 to 42 days of age is the crucial period for Muscovy ducks, and the ability of metabolism and antioxidants were significantly enhanced in liver.